Biological control: Sustainably controlling pests in the vegetative phase of corn - Miranda, Hellem Ranny Nascimento; Sousa, Emylle Stefane Borges de; Santana, Gustavo de Godoi (Seven Editora, 2024)
Brazil is considered the country with the greatest agricultural potential in the world, as it is in a region with a tropical climate, and this contributes positively to the increase in agriculture. Among the numerous segments of the production chain, corn stands out as one of the main grains produced in the country. The continuous cultivation of grass leads to a high incidence of pests, significantly affecting the productive potential of the crop and great losses to producers. A viable alternative to sustainably control these undesirable insects is biological control, allowing to reduce the population density of another organism, through living beings or natural substances, thus acting as pest control agents in agriculture, promoting balance in the crop and contributing to the reduction of agrochemicals in the field, favoring sustainability. since chemical pesticides are harmful to crops and human health. DOI:https://doi.org/10.56238/sevened2023.001-007